Editorial - Aguirre Chávez, Felipe (2020)
The wonderful educational and spiritual adventure” of the Marist Brothers, born on January 2, 1817 in La Valla -France-, materialized in our land with the birth certificate of the Marcelino Champagnat University, on January 5, 1990. The Law No. 25180 allowed materializing this desire to commit to the country in the mission of training competent professionals, committed to a fair and fraternal society and in the vision of being a Marist university community recognized as a leader in the training of professionals with a high academic level. and research, which are committed to building a caring and fair society, within the freedom to think, create, educate and serve human development.